1992
DOI: 10.1111/j.2042-7174.1992.tb00579.x
|View full text |Cite
|
Sign up to set email alerts
|

A self medication scheme for elderly patients improves compliance with their medication regimens

Abstract: This study of elderly patients discharged from hospital looked at the effect of a self medication (SM) scheme on compliance with drug regimens. Patients from four medical wards for the elderly were recruited. Those from two wards participated in a SM scheme (18 subjects). Patients from the other wards (15) acted as controls. Two weeks after discharge, compliance was significantly better in the SM group. Only 6 per cent (one patient) made serious errors compared with 47 per cent of controls. After three months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Wood [21] Compliance Significantly fewer patients rated as non-compliant in SAG compared to controls. Controls made more serious errors…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Wood [21] Compliance Significantly fewer patients rated as non-compliant in SAG compared to controls. Controls made more serious errors…”
Section: Resultsmentioning
confidence: 96%
“…Of the studies subjected to statistical analysis, four reported a significant difference [18,19,21,23]. Although a P value of 0.02 is quoted by D'Altroy et al, it is not clear whether this relates to significance between both groups at all levels of compliance.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations